Open source repositories: Implications for libraries - A.N., Zainab (2010)
Software that is accepted as “Open source” should comply with 10 conditions which are itinerated in the paper. The paper subsequently describes the application of open source initiatives in the digital library context. Three open source digital library initiatives developed by the Digital Library Research Group at the Faculty of Computer Science and information Technology, University of Malaya are highlighted. These are; (a) MyManuskrip: digital library of Malay manuscripts; (b) MyAIS : Digital library of Malaysian scholarly journals and conference proceedings; and (d) DSpace@Um: a digital library of dissertations, theses and final year project reports. Other “free” systems such as EJUM: electronic journal of university of Malaya is also described to highlight the slight difference between open source and being free. The paper also describes the libraries involved in the initiatives and the changing eco-system which libraries must accept to embrace the open source culture.